Simulation study on matrix acidification of heterogeneous reservoirs based on seepage-acid etching coupled discrete virtual internal bond - Yujie Yan; Yanling Wang; Na An (PLoS ONE, 2026)
Matrix acidification is one of the important means for carbonate reservoir modification and permeability increase, and the growth behavior of wormhole determines the effect of matrix acidification. In order to have a deeper understanding of the expansion law of acidified wormhole, this paper carried out numerical simulation of matrix acidification based on the seepage-acid etching coupled discrete virtual internal bond model, and analyzed the influence of matrix acidification on the growth and evolution of acid etched wormhole during matrix acidification in heterogeneous reservoirs. It was found that the enhancement of the heterogeneity of matrix porosity will lead to an increase in wormhole branches and complexity in the acidification process, and the corresponding acid breakthrough time will also become longer. When the anisotropy of the reservoir is strong, there are obvious master wormhole growing perpendicular to the anisotropic direction, and the wormhole morphology is relatively simple. Natural cracks have a strong guiding effect on acid etched wormhole. The results of this paper further reveal the growth law of acid etched wormhole pores, which provides a theoretical understanding for the construction of on-site matrix acidification.